ROLE OF PROPHYLACTIC ANTIBIOTICS IN LOW RISK ELECTIVE LAPAROSCOPIC CHOLECYSTECTOMY: IS THERE A NEED? - Naqvi, Muhammad Ali; Mehraj, Adnan; Ejaz, Raja; Mian, Amer (Journal of Ayub Medical College Abbottabad, 2013)
Background: Elective cholecystectomy for symptomatic gall stone disease carries low risk of postoperative infective complications. Yet the routine use of prophylactic antibiotic is in vogue in many centres. The aim of this study was to find out the efficacy of antibiotic prophylaxis in preventing postoperative infective complications in low risk elective laparoscopic cholecystectomy patients. Method: Randomised controlled trial was carried out in our hospital from 1st Nov 2009 to 15th Oct 2011. A total of 350 patients were included in the study and were divided into Group A (n=177), and Group B (n=173). Group A was given single dose of injection Cefuroxime 1.5 gm as prophylactic antibiotic at the time of induction of anaesthesia, and Group B was not given any antibiotic. In both groups, age, sex, duration of surgery, American Society of Anesthesiologists classification, duration of surgery and length of hospital stay were recorded. Patients were followed-up weekly for 4 weeks and rates of superficial surgical site infections as well as intra-abdominal infections were recorded. Results: There were no significant differences in both groups in terms of age, sex, duration of surgery, length of hospital stay. Eight (4.5%) cases of superficial surgical site infection were noted in Group A and 7 (4.0%) in Group B which was insignificant statistically (p>0.05). Conclusion: In low risk patients antibiotic prophylaxis does not seem to affect the incidence of postoperative infective complications in elective laparoscopic cholecystectomy. The use of prophylactic antibiotics should be reserved for high risk patients undergoing laparoscopic cholecystectomy. Keywords: Antibiotic Prophylaxis, Cholecystectomy, Laparoscopy